Sleep deprivation and recovery sleep affect healthy male resident’s pain sensitivity and oxidative stress markers: The medial prefrontal cortex may play a role in sleep deprivation model - Chen, Shuhan; Xie, Yanle; Li, Yize; Fan, Xiaochong; Xing, Fei; Mao, Yuanyuan; Xing, Na; Wang, Jingping; Yang, Jianjun; Wang, Zhongyu; Yuan, Jingjing (Frontiers in Molecular Neuroscience, 2022)
Sleep is essential for the body’s repair and recovery, including supplementation with antioxidants to maintain the balance of the body’s redox state. Changes in sleep patterns have been reported to alter this repair function, leading to changes in disease susceptibility or behavior. Here, we recruited healthy male physicians and measured the extent of the effect of overnight sleep deprivation (SD) and recovery sleep (RS) on nociceptive thresholds and systemic (plasma-derived) redox metabolism, namely, the major antioxidants glutathione (GSH), catalase (CAT), malondialdehyde (MDA), and superoxide dismutase (SOD). Twenty subjects underwent morning measurements before and after overnight total SD and RS. We found that one night of SD can lead to increased nociceptive hypersensitivity and the pain scores of the Numerical Rating Scale (NRS) and that one night of RS can reverse this change. Pre- and post-SD biochemical assays showed an increase in MDA levels and CAT activity and a decrease in GSH levels and SOD activity after overnight SD. Biochemical assays before and after RS showed a partial recovery of MDA levels and a basic recovery of CAT activity to baseline levels. An animal study showed that SD can cause a significant decrease in the paw withdrawal threshold and paw withdrawal latency in rats, and after 4 days of unrestricted sleep, pain thresholds can be restored to normal. We performed proteomics in the rat medial prefrontal cortex (mPFC) and showed that 37 proteins were significantly altered after 6 days of SD. Current findings showed that SD causes nociceptive hyperalgesia and oxidative stress, and RS can restore pain thresholds and repair oxidative stress damage in the body. However, one night of RS is not enough for repairing oxidative stress damage in the human body.